Circulating tumor cells detected with a microcavity array predict clinical outcome in hepatocellular carcinoma. (6th March 2021) - Takahashi, Kazuto; Ofuji, Kazuya; Hiramatsu, Katsushi; Nosaka, Takuto; Naito, Tatsushi; Matsuda, Hidetaka; Endo, Katsuya; Higuchi, Masayuki; Ohtani, Masahiro; Nemoto, Tomoyuki; Nakamoto, Yasunari
Abstract: The present study aimed to establish a novel isolation strategy for circulating tumor cells (CTCs) using a microcavity array (MCA) system and to evaluate the clinical significance of CTCs in hepatocellular carcinoma (HCC). We examined recovery rates of HCC cell lines spiked into whole blood in MCA assay. Circulating tumor cells were isolated from peripheral blood samples (3 mL) of 7 healthy donors (HD), 14 patients with liver cirrhosis (LC), and 31 patients with HCC using the MCA system. Additionally, we investigated the mRNA expression of liver‐specific genes in isolated CTCs using qPCR. The recovery rates were 65.1% (HepG2), 76.7% (HuH7), and 99.0% (PLC/PRF/5). In HD and patients with LC and HCC, the CTC positivity rate (CTCs ≥10) and average CTC number were as follows: HD 0% and 0.1, LC 14.3% and 5.3, HCC 54.8% and 47.6, respectively. The CTC positivity rate in HCC was significantly higher than that in LC ( p < 0.05). The number of CTCs was significantly higher in metastatic HCC (102.2 ± 160.6) than in localized HCC (8.2 ± 7.7) ( p < 0.05). The expression of AFP, glypican ‐ 3, EpCAM, and albumin ( ALB) genes was detected in isolated CTCs. The positive CTCs (CTCs ≥10) significantly reduced the cumulative survival in patients with HCC ( p = 0.025), especially in localized patients with HCC ( p = 0.046). The newly developed MCA system has the potential to isolate CTCs from HCC with high sensitivity, and mRNA expression could be measured from CTCs. Identification of positive CTCs can help predict clinical outcome of patients with HCC. Thus, analysis of CTCs in patients with HCC may provide important information as a novel biomarker in disease progression. Abstract : This study describes the detection of circulating tumor cells (CTCs) in the peripheral blood of hepatocellular carcinoma (HCC) patients using a newly developed microcavity array. Our results show that a large number of CTCs was detected in metastatic HCC patients, and mRNA expression of AFP, glypican‐3, EpCAM and albumin was detected in detected CTCs. Identification of positive CTCs or ALB mRNA expression can help predict poor prognosis of HCC patients.